Acoustic Gaussian-Airy beams. (29th September 2022) - Chen, Xizhou; Ding, Suyu; Wei, Qinran; Tu, Juan; Guo, Xiasheng; Zhang, Dong
Abstract: Acoustic Airy beams as non-diffractive beams possess self-bending, self-healing, and non-diffraction virtues and are expected to have great potential in applications like ultrasonic imaging. Here an analytical theory is provided for Gaussian modulated Airy (gAiry) acoustic beams. It is revealed through numerical calculations and finite element simulations that gAiry beams inherit the merits mentioned above of standard Airy beams. In theoretically predicted and more practical cases where sources of limited apertures generate beams, reduction of side lobes is found in gAiry fields, while bilateral focusing using a pair of beams shows improved field features when compared with focused Airy fields. The theories and observations here can help deploy gAiry beams in applications.